Small Firm Electricity Demand in Las Cruces, New Mexico, USA - Fullerton, Jr., Thomas M.; Pastor, Daniel J.; Pokojovy, Michael; Yurachek, Andrew T. (Pontificia Universidad Católica del Perú, 2023)
Research examining small commercial and industrial electricity usage patterns have historically received less attention than residential electricity consumption patterns. This study examines electricity as an input to small firm commercial and industrial (CIS) production in Las Cruces, the second largest metropolitan economy in the state of New Mexico, using annual frequency data from 1978 to 2018. Those data include labor, per capita personal income, price measures for electricity and natural gas, and weather variables. The long-run and short-run elasticities of the data are then estimated using an autoregressive distributed lag model (ARDL). In the long-run, the CIS derived-demand curve is found to be upward sloping, and Las Cruces CIS customers use natural gas as a complementary input. Real per capita income is also found to have a positive impact in the long-run, while weather impacts are found to be ambiguous. In the short-run, the Las Cruces CIS derived-demand curve is downward sloping, CIS customers use natural gas as a substitute factor, and weather extremes are found to be positively correlated with small firm electricity usage.
Keywords: Derived Input Demand; Duality Theory; Electricity; Las Cruces Metropolitan Economy; https://purl.org/pe-repo/ocde/ford#5.02.01